Globalization, Cosmopolitanism and Environment: Critical Review of Ulrich Beck - Niloofar Hashemi; Mohammad Saeid Zokaei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
It is not possible to address the issue of the environment in an empty space, especially when the environmental challenges such as climate change can only be analyzed and explained on a global scale. Nowadays, the concept of globalization is very interesting for the social theorists, and over time the fundamental challenges of “question about its existence or non-existence” have steadily increased. This article will take a look at one of the most diverse ideas in this field, the concept of Ulrich Beck’s cosmopolitanism, with an emphasis on its ecological dimensions, which he considers to be a worthy alternative to the concept of globalization, and goes so far as to it re-creates a different frame of reference for contemporary sociology. The article deals with the description of Beck’s ideas on the concept of global risk society and its characteristics, the fundamental differences between globalization and cosmopolitanism, the cosmopolitanism process and the sociology of cosmopolitanism, and finally, a brief look at several critiques of his theory. Then it is focused on comparative research of the ecological dimensions of globalization in the ideas of Harvey, Giddens, Robertson and Beck. This article introduces three novel models of conflict, interwoven, and subset between environmental discourse and economic discourse.